Evolving Trend of Domicile and Nationality in Private International Law with special reference to Nepal - Baral, Sagar (Nepal Public Policy Review, 2022)
Understanding the domicile and nationality is the key to properly adjudicating a case involving a foreign element by the judiciary. In this milieu, this paper aspires to analyse the concept of domicile and nationality with its evolving trend and evaluate the Nepalese judicial and legal policy on domicile and nationality through observation of international and local practices. Furthermore, this paper aims to trace the current policy gap in the legal and judicial interpretation of the domicile and nationality in the Nepalese context, including the citizenship bill. The paper concludes that connecting factors need to be used contextually on a case-to-case basis with proper policy genesis. It also prescribes key recommendations to address existing gaps, such as interpreting the habitual residence and nationality, domesticating the various Convention on the PIL such as Hague Conference on PIL, Law Applicable to Matrimonial Property Regimes, 1978, Celebration and Recognition of the Validity of Marriage, 1978, etc.